Production, Properties and Application of Blends of Palm Stearin with Palm Kernel Olein, Sunflower Oil or Anhydrous Milkfat Transesterified by Lipases - Lai, Oi Ming (1998)
Palm stearin, the cheaper and more solid fraction of palm oil, is a useful hard fat in the manufacture of edible fat such as margarine. However, with slip melting points ranging between 46 to 56°C, only 10% of palm stearin can be added to a standard table margarine. This study was conducted to investigate the performance of lipase-catalysed transesterified fat blends containing high levels of palm stearin (minimum 40%) when processed into table margarine. In the first part of the work, the effect of several reaction conditions on lipase-aided transesterification of palm stearin was studied. Results on the effect of lyophilisation of enzyme on transesterification indicated increases in % triglyceride (TG) when drying time was increased. The maximum yield was at 4 or 6 hours of drying. Studies on the effect of reaction time indicated that 8h of reaction produced the highest % TG remaining and Rhizomucor miehei and A lcaligenes lipases both showed maximum rates at 6h reaction time. The transesterification process also decreased the slip melting point (SMP) of palm stearin slightly after 24h reaction with R. miehei lipase registering the largest decrease (5.5°C) compared to the initial unreacted mixture. The catalytic stability of R. miehei and Pseudomonas lipases, after being subjected to ten runs of repeated usage indicated that the lipases can be reused to produce fairly constant products on a large scale. The rates of transesterification were found to vary with different lipase sources. Bacterial lipase of Pseudomonas was found to have the fastest rate of reaction (50.0h⁻¹) followed by R. miehei lipase (27.1h⁻¹). Generally, both the above lipases also produced the highest degree of transesterification and % FFA. Pseudomonas lipase-catalysed mixtures caused the biggest drop in SMP and solid fat content (SFC) in all the three mixtures studied.